Figure 3 from: Haukisalmi V, Konyaev S, Lavikainen A, Isomursu M, Nakao M (2016) Description and life-cycle of Taenia lynciscapreoli sp. n. (Cestoda, Cyclophyllidea). ZooKeys 584: 1-23. https://doi.org/10.3897/zookeys.584.8171 - Haukisalmi, Voitto; Konyaev, Sergey; Lavikainen, Antti; Isomursu, Marja; Nakao, Minoru (Zenodo, 2016)
Figure 3 - Scolex (A, B) and a pregravid proglottid with uterus (C) of Taenia lynciscapreoli sp. n. from Lynx lynx. A, B paratypes C voucher. Scale-bars: 200 μm (A–B); 500 μm (C).